Protective Effects of Abrus cantoniensis Hance on the Fatty Liver Hemorrhagic Syndrome in Laying Hens Based on Liver Metabolomics and Gut Microbiota - Liu, Xu; Pan, Yinchuan; Shen, Youming; Liu, Hailong; Zhao, Xinghua; Li, Jianyong; Ma, Ning (Frontiers in Veterinary Science, 2022)
As a metabolic disease, fatty liver hemorrhagic syndrome (FLHS) has become a serious concern in laying hens worldwide. Abrus cantoniensis Hance (AC) is a commonly used plant in traditional medicine for liver disease treatment. Nevertheless, the effect and mechanism of decoction of AC (ACD) on FLHS remain unclear. In this study, ultra-high performance liquid chromatography analysis was used to identify the main phytochemicals in ACD. FLHS model of laying hens was induced by a high-energy low-protein (HELP) diet, and ACD (0.5, 1, 2 g ACD/hen per day) was given to the hens in drinking water at the same time for 48 days. Biochemical blood indicators and histopathological analysis of liver were detected and observed to evaluate the therapeutic effect of ACD. Moreover, the effects of ACD on liver metabolomics and gut microbiota in laying hens with FLHS were investigated. The results showed that four phytochemicals, including abrine, hypaphorine, vicenin-2 and schaftoside, were identified in ACD. ACD treatment ameliorated biochemical blood indicators in laying hens with FLHS by decreasing aspartate aminotransferase, alanine aminotransferase, triglycerides, low-density lipoprotein cholesterol and total cholesterol, and increasing of high-density lipoprotein cholesterol. In addition, liver lipid accumulation and pathological damages were relieved in ACD treatment groups. Moreover, distinct changes in liver metabolic profile after ACD treatment were observed, 17 endogenous liver metabolites mainly associated with metabolism of arachidonic acid, histidine, tyrosine and tryptophan were reversed by ACD. Gut microbiota analysis revealed that ACD treatment significantly increased bacterial richness (Chao 1, P < 0.05; Ace, P < 0.01), and up-regulated the relative abundance of Bacteroidetes and down-regulated Proteobacteria, improving the negative effects caused by HELP diet in laying hens. Taken together, ACD had a protective effect on FLHS by regulating blood lipids, reducing liver lipid accumulation, and improving the dysbiosis of liver metabolomics and gut microbiota.